Unveiling the inflammatory messengers after intracerebral hemorrhage: the crosstalk between peripheral NETs and microglia - Zhang, Shanshan; Jin, Ziqi; Jiang, Li; Zhang, Yibin; Wu, Tong; Xu, Peng; Cui, Yabin; Zhang, Dongmei; Lu, Jing (Frontiers in Immunology, 2025)
Intracerebral hemorrhage (ICH), a common neurological disorder with a high rate of disability, involves complex immunoinflammatory mechanisms, particularly those related to secondary inflammatory injury. Neutrophils, as the earliest subtype of leukocytes recruited after stroke, play a pivotal role in secondary brain injury. Traditionally, neutrophils were thought to mediate tissue damage primarily via phagocytosis, chemotaxis, and degranulation. However, recent studies have shown that neutrophils also contribute to the pathogenesis of intracerebral hemorrhage by releasing neutrophil extracellular traps (NETs), which exacerbate blood-brain barrier disruption, amplify local inflammy -30ation, and promote neuronal injury. This review systematically examines the interactions between the central and peripheral immune systems following ICH. It focuses on the bidirectional regulatory relationship between microglia and neutrophils, and their coordinated roles in inflammation, blood-brain barrier disruption, neurological dysfunction, and cognitive impairment. In addition, this review summarizes recent potential therapeutic strategies targeting the formation and clearance of NETs, including peptidylarginine deiminase 4 inhibitors, reactive oxygen species inhibitors, histone inhibitors, and DNases. These interventions may offer theoretical insights into novel therapeutic targets for mitigating secondary injury following ICH.